Adverse effects of hyperbilirubinemia on the development of healthy term infants - I Made Arimbawa; Soetjiningsih Soetjiningsih; I K Kari (Indonesian Pediatric Society, 2006)
Background Indirect hyperbilirubinemia is a common problem dur-ing the neonatal period and may cause long-term abnormality ordevelopmental delay.Objective To evaluate the adverse effects of hyperbilirubinemiaon the development of healthy term infants.Methods This was a prospective cohort study on healthy terminfants born in Sanglah Hospital, Denpasar. Mullen Scale Testswere performed at the ages of 3 and 6 months to assess subjects’development. Bivariate and multivariate analyses were conductedto examine the relationship between several dependent variablesand developmental outcomes.Results One hundred and twelve infants were enrolled in this study[56 with hyperbilirubinemia, 56 without hyperbilirubinemia; 58 (52%)male, 54 (48%) female]. Mean birth weight was 318.3 grams (SD342.26) vs 3162.5 grams (SD 338.61). At the age of 3 months,below average category according to Mullen Scale Test was higherin infants with history of hyperbilirubinemia compared to those with-out hyperbilirubinemia, which was statistically significant for finemotor scale (17.9% vs 5.4%; respectively; P=0.039; RR 1.66; 95%CI 1.15;2.39). At 6 months of age, it was higher in infants withhistory of hyperbilirubinemia compared to those without hyperbi-lirubinemia and this was statistically significant for gross motor scale(19.6% vs 3.6%, respectively; RR 1.86; 95%CI 1.36; 2.56; P=0.008)and fine motor scale (17.9% vs 5.4%, respectively; RR 1.66; 95%CI1.15; 2.39; P=0.039). Multivariate logistic regression test showedthat only hyperbilirubinemia was correlated with gross motor scaledelay at the age of 6 months (P=0.027; OR 5.97; 95%CI 1.22;29.12).Conclusion Healthy term infants with history of hiperbilirubinemiawere associated with increased gross motor scale delay at theage of 6 months